2020
DOI: 10.1038/s41598-020-76962-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrode and dielectric layer interface device engineering study using furan flanked diketopyrrolopyrrole–dithienothiophene polymer based organic transistors

Abstract: We successfully demonstrated a detailed and systematic enhancement of organic field effect transistors (OFETs) performance using dithienothiophene (DTT) and furan-flanked diketopyrrolopyrrole based donor–acceptor conjugated polymer semiconductor namely PDPPF-DTT as an active semiconductor. The self-assembled monolayers (SAMs) treatments at interface junctions of the semiconductor–dielectric and at the semiconductor–metal electrodes has been implemented using bottom gate bottom contact device geometry. Due to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…30,31 This can help to alleviate the hysteresis in the transfer characteristics by reducing the trap density at the electrode/semiconductor layer interface. 32,33 Due to the influence of the SAM treatment on the hydrophobicity of the electrode, it is anticipated that the morphology of the semiconducting layer formed on the SAM-treated electrode will be changed. 34 Therefore, we examined the morphology of the semiconducting layer formed on both the untreated and SAM-treated Au electrodes using atomic force microscopy (AFM) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 This can help to alleviate the hysteresis in the transfer characteristics by reducing the trap density at the electrode/semiconductor layer interface. 32,33 Due to the influence of the SAM treatment on the hydrophobicity of the electrode, it is anticipated that the morphology of the semiconducting layer formed on the SAM-treated electrode will be changed. 34 Therefore, we examined the morphology of the semiconducting layer formed on both the untreated and SAM-treated Au electrodes using atomic force microscopy (AFM) as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is attributed to an improvement in the molecular orientation of PNDI-TVT by PFBT. 22,33 To investigate the changes in the microstructure of the PNDI-TVT films formed on untreated and SAM treated Au electrodes, we measured Grazing-Incidence Wide-Angle X-ray Scattering (GIWAXS) patterns for both types of films. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the oxide dielectrics, there are an abundance of carrier trap groups on their surfaces, for example, −OH groups on the SiO 2 substrate. , Utilizing a passivation layer is a simple but effective method to eliminate the adverse impact of −OH groups on OFET performance. Maeda et al reported the use of n -doped LaB 6 as a passivation layer to passivate interfacial traps.…”
Section: Lowering the Trap Densitymentioning
confidence: 99%
“…These substances are also highly efficient in hole transport, photoconductors, study of interface engineering, and so on. 58,59 Moreover, the conjugated microporous polymers (CMPs) are easy to functionalize and poses various applications like organic electronics, photovoltaics, sensing and so forth, and it has been noticed that through the incorporation of fused thiophenes into the CMPs enhanced their performances. [60][61][62][63] To this context, the research groups of Ozturk & Thomas have constructed DTT-CMPs by means of bulk and electrochemical oxidative polymerization reactions (Scheme 1).…”
Section: Dtt-based Molecules and Their Potential Applicationsmentioning
confidence: 99%